2009
DOI: 10.1007/s00228-009-0647-2
|View full text |Cite
|
Sign up to set email alerts
|

Prescription of drugs during pregnancy: a study using EFEMERIS, the new French database

Abstract: Background Because of the limited data concerning drug risks in pregnancy, health professionals are often deprived of relevant and sufficient information related to prescribing or dispensing during pregnancy. However, previous studies have emphasised the widespread French prescription of several drugs (sometimes "typically French") which have not been assessed in pregnant women. Objectives The aim of the present study was to create the first French database of drugs prescribed and dispensed during pregnancy an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
83
0
11

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 121 publications
(101 citation statements)
references
References 16 publications
7
83
0
11
Order By: Relevance
“…However, to be reimbursed the drugs need to be prescribed, which excludes capture of drugs obtained OTC. This is illustrated by a study reported by Lacroix et al who did not succeed in assessing OTC use during pregnancy using the French health insurance reimbursement database of southeastern France [9]. Furthermore, certain prescription-only drugs, for example thirdgeneration oral contraceptives, are prescription-only but are not reimbursed.…”
Section: Discussionmentioning
confidence: 99%
“…However, to be reimbursed the drugs need to be prescribed, which excludes capture of drugs obtained OTC. This is illustrated by a study reported by Lacroix et al who did not succeed in assessing OTC use during pregnancy using the French health insurance reimbursement database of southeastern France [9]. Furthermore, certain prescription-only drugs, for example thirdgeneration oral contraceptives, are prescription-only but are not reimbursed.…”
Section: Discussionmentioning
confidence: 99%
“…Engeland et al [7] found that among more than 100,000 pregnant women in Norway in 2004 -2006, approximately 57 % received a prescription medication. Studies from France and Germany showed an even higher rate of more than 85 % [6,15] .…”
Section: Introductionmentioning
confidence: 93%
“…La cohorte Éva-luation chez la femme enceinte des médicaments et de leur risque (EFEMERIS) [8] a pour but de détecter les médicaments à risque pour le foetus et d'assurer un rôle d'alerte sur le plan des effets malformatifs mais également d'apporter des informations sur des médicaments encore mal évalués. Initiée en 2004, 48 000 femmes, ayant accouché en Haute-Garonne, ont ainsi été incluses dans l'étude.…”
Section: Les Cohortes : Un Outil Irremplaçable En Santéunclassified